2006
DOI: 10.1111/j.1365-313x.2006.02813.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for a flavin‐containing mono‐oxygenase in resistance against microbial pathogens in Arabidopsis

Abstract: SummaryUsing activation tagging in the Arabidopsis Col-0 rps2-101C background, we identified a mutant (FMO1-3D) that showed virtually no symptoms after inoculation with virulent Pseudomonas syringae pv. tomato DC3000 bacteria. The dominant, gain-of-function phenotype of the FMO1-3D mutant is due to over-expression of a class 3 flavin-containing mono-oxygenase (FMO). We recapitulated the FMO1-3D mutant phenotype in independent transgenic Col-0 lines over-expressing the FMO1 cDNA under the control of the 35S CaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 51 publications
4
93
0
3
Order By: Relevance
“…A largely Pip/FMO1-independent activation of the SA defense pathway at pathogen inoculation sites might explain why defects in Pip biosynthesis and FMO1 result in comparatively moderate decreases of basal immunity. In fact, the importance of FMO1 for local plant immune responses is variable and depends on the nature of the attacking pathogen, with particular significance of FMO1 for local immunity to pathogens that activate EDS1-dependent and SA-independent branches of plant defense (Bartsch et al, 2006;Koch et al, 2006). Interestingly, EDS1 and its interacting partner PAD4, both master regulators of basal immunity (Feys et al, 2001), have also been identified as necessary SAR components (Mishina and Zeier, 2006;Jing et al, 2011;Rietz et al, 2011;Breitenbach et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A largely Pip/FMO1-independent activation of the SA defense pathway at pathogen inoculation sites might explain why defects in Pip biosynthesis and FMO1 result in comparatively moderate decreases of basal immunity. In fact, the importance of FMO1 for local plant immune responses is variable and depends on the nature of the attacking pathogen, with particular significance of FMO1 for local immunity to pathogens that activate EDS1-dependent and SA-independent branches of plant defense (Bartsch et al, 2006;Koch et al, 2006). Interestingly, EDS1 and its interacting partner PAD4, both master regulators of basal immunity (Feys et al, 2001), have also been identified as necessary SAR components (Mishina and Zeier, 2006;Jing et al, 2011;Rietz et al, 2011;Breitenbach et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The strongly pathogen-inducible FMO1 gene encodes a flavin monooxygenase that is activated in both locally inoculated and distal leaves (Bartsch et al, 2006;Koch et al, 2006;Mishina and Zeier, 2006). Notably, functional FMO1 is necessary for SA accumulation in the systemic, noninoculated leaves but dispensable for SA production in inoculated tissue (Mishina and Zeier, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our data also show that intact phytochrome signaling is required for pathogen-induced expression of FMO1 in noninoculated leaves. FMO1 is required for SAR in Arabidopsis, its overexpression confers increased plant resistance, and mutant plants unable to express the gene in distant tissue after a local infection, including phyAphyB, are all SAR deficient (Bartsch et al, 2006;Koch et al, 2006;Mishina and Zeier, 2006). During the SAR process, long-distance signal(s) generated in inoculated leaves are thought to travel through the plant and trigger resistance in distant tissue (Grant and Lamb, 2006;Park et al, 2007).…”
Section: Cross Talk Of Photoreceptor Signaling and Plant Defensementioning
confidence: 99%
“…FMOs have also been found in plants and fungi. Plant FMOs are involved in the biosynthesis of the plant-growth hormone auxin (6, 7) and in pathogen defense (8)(9)(10). In fungi, FMOs are vital for the functional expression of proteins that contain disulfide bonds by controlling the redox potential within the endoplasmic reticulum (11)(12)(13).…”
mentioning
confidence: 99%